If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x) = 5x x = 5x Solving x = 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. x + -5x = 5x + -5x Combine like terms: x + -5x = -4x -4x = 5x + -5x Combine like terms: 5x + -5x = 0 -4x = 0 Divide each side by '-4'. x = 0 Simplifying x = 0
| 6d-5-(5-3d)= | | 5x-4=86 | | S=2(pi)rh | | 3=LW | | y/6=x | | 2g=W | | m-16=n | | 16x(78+54)= | | 14+n=m | | 2y+5x=25 | | ax(bxc)=(axb)xc | | x=y-18 | | b=10+y | | b-5=a | | 7(x+5)-3=4 | | 7+n=m | | c=y-15 | | x-5/4=5/6 | | -9x-10y-3x+5y/8x=0 | | -9x-10y-3x+5y/8x | | ln(x)=2.44 | | x+(1.502-x)=1.216 | | x+4x+3x=31 | | x*(2.4184-x)=1.9383 | | y=(5-x)(2-3x) | | x+(2.4184-x)=1.9383 | | 4=-6+7x | | x+18+4x=-37-4x-44 | | 5.0+0.2x=3.5x^2 | | X^2+17x-72=0 | | 477=-6+3(n+1) | | y^2-11y-80=0 |